Compromised immune response to viral infections in type 2 diabetes mellitus - Ambati, Sudhir Kumar (International Journal Of Community Medicine And Public Health, 2020)
Viral infections are common in people with type 2 diabetes, which is associated with poor immune responses. In type 2 diabetes, the normal functioning of the immune system and immune cells is suppressed, which allows the viruses to enter the host cells and cause infections. The impacts of type 2 diabetes on immune response and viral infections are associated with different mechanisms, including suppression or impairment of cytokine production, dysfunctioning of immune cells, defects in the phagocytosis, and disruption of natural killer cells. The high concentration of blood glucose or hyperglycemia in type 2 diabetes affects the production of cytokines, including interleukins, interferon, TNF-α, and IFN-γ. These cytokines are involved in fighting pathogens, and they induce the production of antibodies involved in the adaptive immune response. Therefore, disruption of these cytokines production leads to compromised immune response and invading pathogens like viruses enter and replicate in the host body.